Emergence and mating behavior of the oriental fruit moth Cydia molesta (Lepidoptera: Tortricidae) and its potential for reproduction. Issue 5 (3rd September 2019) - Kong, Weina; Wang, Yi; Jia, Xiaoting; Gao, Yue; Fan, Renjun; Li, Jie; Ma, Ruiyan
Summary: The Oriental fruit moth, Cydia molesta (Busck, 1916) (Lepidoptera: Tortricidae), is a key pest of fruit and is widely distributed around the world. There are important connections between its behavior and biology and its management in agriculture, but few studies have investigated the associations between adult behaviors and oviposition. In this study, adult emergence, mating, and reproduction were investigated under laboratory and field conditions. The ratio of females to males at eclosion was approximately 1:1. When one virgin female had access to one virgin male, 66% and 34% of the couples copulated just once and twice, respectively; and the infertility rate of eggs (21.39 ± 1.25%) did not vary daily. Males, given access to one new female daily, could copulate multiple times, whereas females seldom mated more than once, indicating a male-biased operational sex ratio, but mating status of the male parent had no effect on progeny egg reproduction. Also, the number of eggs that hatched by all female partners of a male was inversely proportional to copulation duration for the female laying the eggs for total female reproductive success; and the number of eggs laid by all female partners of a male was proportional to their number of matings for total male reproductive success. However, the total number of eggs that hatched did not significantly differ for eggs laid by a female given new virgin males daily for mating (17.75 ± 4.28) versus eggs laid by virgin females (19.17 ± 7.51) presented daily with a male that re-mated daily with the series of females. Therefore, our results showed that females engaged in mate choice and males engaged in mate competition, affecting egg production, a factor that may be used to enhance mating disruption technology against Cydia molesta .